SIA “ Limbažu siltums” finanšu analīze - Grundberga, Gita (Latvijas Universitāte, 2020)
Diplomdarba mērķis bija veikt SIA “Limbažu siltums” saimnieciskās darbības finanšu analīzi un un izstrādāt priekšlikumus finanšu radītāju uzlabošanai. Darba mērķa sasniegšanai risināti šādi uzdevumi: • izpētīt finanšu analīzes teorētiskos aspektus; • uzņēmumu SIA “Limbažu siltums” un SIA “Saldus siltums” finanšu pārskatu rādītāju analīzi; • izvērtēt un izstrādāt priekšlikumus SIA “Limbažu siltums” finanšu rādītāju uzlabošanai. Galvenais secinājums - uzņēmumam SIA “Limbažu siltums” ir lielas problēmas tieši ar debitoru parādiem, jo uzņēmumā nav izstrādātas kredītpolitikas. Galvenie priekšlikumi - galvenokārt uzņēmumam jāstrādā ar debitoru parādiem,kas uzlabotu siltuāciju ar likviditātes un maksātnespējas risku, uzlabotu rentabilitātes rādītājus. Darbs sastāv no 76 lappusēm, 2 attēliem, 30 tabulām, 7 pielikumiem un 27 izmantotiem literatūras avotiem.

The subject of the diploma work is the financial analysis of Ltd “Limbazu siltums”. The diploma work has a theoretical analysis of the nature of the financial analysis, as well as an analysis of the financial performance of the individual and comparable company. The diploma consists of three chapters. The first chapter examines the theoretical aspects of financial analysis. The second chapter examines the economic activity of the Ltd “Limbazu siltums”. The author describes in detail the financial analysis figures as well as the parameters described in the calculation to assess the financial situation of the Ltd “Limbazu siltums” and “Saldus siltums”. The conclusion of the diploma results in conclusions as well as the development of proposals to improve the financial situation of the company. The main conclusion is that the company “Limbazu sltums” has big problems, precisely with receivables, as their fighting time is relatively long. During the period under study, the customer debt ratio has tended to grow and this is positive, as this means that receivables are being collected more quickly. However, this ratio is low and indicates that there is no credit policy developed in the company. The main proposals - mainly the company must work on receivables and reduce costs that would solve a number of situations, such as liquidity and insolvency risks, and improve profitability rates, as the company would have more resources to cover liabilities. Hiring additional employees who will only work with customers and introduce an additional discount system that would encourage people to settle heat bills more quickly. The work consists of 76 pages, 2 pictures, 30 tables, 7 attachments and 27 literature sources.
Financial analysis of the Ltd “Limbazu siltums”
Keywords: Ekonomika; likviditāte; rentabilitāte; finanšu rādītāju analīze; siltumenerģija; horizontālā analīze